Supporting patients in making treatment decisions for early prostate cancer: a qualitative study of healthcare professionals' views on barriers and challenges in an Asian country - Lee, Ping Yein; Cheong, Ai Theng; Ng, Chirk Jenn; Lee, Yew Kong; Lim Abdullah, Khatijah; Abdul Razack, Azad Hassan; Ong, Teng Aik (Mary Ann Liebert, 2016)
Background: The aim of this study is to explore the challenges faced by healthcare professionals (HCPs) in Malaysia in supporting patients with early prostate cancer in making treatment decisions. Methods: Four in-depth individual interviews and three focus group discussions were conducted with urologists (n=11), urology trainees (n=5), oncologists (n=3) and policy makers (n=1) in Malaysia in 2012-2013. A semi-structured interview guide was used to facilitate the interviews, which were audio-recorded, transcribed verbatim and checked. Thematic approach was used to analyze the data. Results: Challenges reported by HCPs in supporting patients in making decisions about prostate cancer treatment consisted of patient, social, healthcare professionals and health system factors. Patient-related challenges were: distrust of HCPs, difficulty in communicating information, preconceptions, attitudes to treatment, preparedness for decision making, viewing prostate cancer as taboo and fear of treatment complications, or side-effects. Social factors, such as influence of family or others, also posed a problem for HCPs seeking to support patients’ decision-making. HCP-related challenges included: differences of opinion among HCPs, uncertainty about the best treatment option and lack of interdisciplinary cooperation. Healthcare system factors challenges included: lack of support staff, time constraints, treatment availability and treatment costs. HCPs suggested that delivery of care by multi-disciplinary teams, and more use of audio-visual media, would help patients to make decisions. Conclusions: HCPs faced various challenges in supporting patients with prostate cancer in making decisions about treatment. Delivery of care by a supportive team in a specialist centre may improve the support patients receive in making decisions.